Beehive wind turbine: A new design for electric power generation in urban and semi-urban zones. Issue 5 (October 2022) - Monzamodeth, Román-Sedano A; Nicolás Iván, Román-Roldán; Bernardo, Hernández-Morales; Osvaldo, Flores; Fermín, Castillo; Bernardo, Campillo
A new wind turbine design for domestic use in urban and semi-urban areas has been studied to examine their implementation and efficiency. In this work, the development of a wind turbine, based on the beehive shape is proposed for possible domestic implementation in urban and semi-urban zones. A first prototype is presented and results of testing it in a mobile assembly are reported. The wind turbine was designed using CAD and to compute the air flow pressure distribution on the blades and assess the mechanical response of the turbine, computational fluid dynamics (CFD) and static structural simulations were performed. The CFD results showed pressure on all the wind turbine blades and a small pressure increase in the cavities generated by the beehive arrangement. On the other hand, the prototype was manufactured using a 3D printer and tested under working conditions on a mobile assembly in urban and semi-urban routes (freeway and highway, respectively). The revolutions per minute of the turbine and the relative wind velocity were measured and employed for structural simulations. The results demonstrated that the proposed beehive wind turbine is able to operate on urban and semi-urban areas.